The Implementaion of Google Form as an Evaluation Tool by English Language Teachers at SMPN 5 Tarakan - Ulfa, Fitrah; Kusmaryani, Woro; Arifin, Arifin (LPPM Universitas Borneo Tarakan, 2022)
This study attempted to outline the benefits and drawbacks of using Google Form as an assessment tool for English classes at SMP N 5 Tarakan. The Google Form itself is a component of a Google features that may gather data from different responses to different purposes, like surveys and task media. This study examined how Google Form could be used as an evaluation, which should make teaching and learning more convenient. The descriptive qualitative method was employed in this investigation. Study of documentation, observation, and interviews were all used in collecting of data, which was then qualitatively assessed using a coding system and narratively recounted. The subjects of this study were English teachers and students who were represented based on the highest scores in English subjects from each class. The results of this study indicated there were both advantages and disadvantages to using Google Form as a tool for learning evaluation by English teachers and student from the planning, preparation, and readiness stages of facilities and infrastructure to the implementation stage, using Google Form had an impact and benefits in terms of effectiveness and efficiency. The Google Form substantially benefited teachers in terms of money, time, and effort. It aided students in completing practical assignments more succesfully and with greater statisfaction.